Classroom Action Research-Based Lesson Study in Determining The Formula of Circle Area - Sunata Sunata (Universitas Sebelas Maret, 2019)
Abstract: The purpose of this study investigated and understand impact of classroom action research- based lesson study in determining the formula of circle area. This kind a classroom action research in the subject of money and bank in order to participate in solving problems related materials. The Subject of this study is Grade 6 student in academic year 2017/2018. The implementation classroom action research conducted in two cycles comprising Planning, Implementation, observing, and reflection stages. The result of this study that classroom action research-based lesson study in determining the formula of circle area has been well implemented including the completeness of the learning tools and preparing the Lesson Plans before teaching on each teaching material. Based on the results of the implementation of classroom action research-based lesson study can be concluded that classroom action research-based lesson study can improve student achievement.